The Influence of Ethnocentrism and Social Culture on the Performance of Local Government Agencies in Serang Regency - Bahrul Ulum; Sunardi; Supriadi, Bambang (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to analyze the effects of ethnocentrism and social culture on the performance of local government agencies in Serang Regency. The research employed a quantitative approach. The population consisted of all residents of Serang Regency aged between 20 and 60 years, totaling 932,137 individuals. A sample of 156 respondents was selected using proportional random sampling. Data were collected through questionnaires distributed to residents of Serang Regency. The collected data were analyzed using the Structural Equation Modeling (SEM) method, which was implemented through the AMOS software program. The results indicate that ethnocentrism has a positive and significant effect on the performance of local government agencies. Furthermore, social culture also has a positive and significant effect on the performance of local government agencies.